The potential price and access implications of the cost-utility and budget impact methodologies applied by NICE in England and ICER in the US for a novel gene therapy in Parkinson's disease. Issue 1 (1st January 2018) - Jørgensen, Jesper; Servos, Spiros; Kefalas, Panos
ABSTRACT: Background : NICE in England, and ICER in the US both use cost-utility analyses (CUA) and budget impact analyses (BIA) to assess value for money and affordability, however the thresholds used differ greatly. Objective : To perform a cross-country comparison of the results of the CUA and BIA and detail the implications for reimbursed price and volumes, for a novel gene therapy for Parkinson's disease (PD). Methods : A Markov model was built to perform country-specific CUAs and BIAs Findings : The US ceiling price identified through CUA is 1.8 times higher than in England (aligning to our previous US/UK price comparison analysis of high-cost drugs). However, the net budget impact corresponding to these price levels would limit number of patients treated in order not to exceed the BIA threshold. Performance-based annuity payments can increase patient access at launch without exceeding the thresholds while reducing payers' data uncertainty. Conclusion : Our cost-utility analysis in PD shows a difference in price potential between the US and England that aligns with what is observed in practice for other high-cost drugs. Furthermore, the budget impact threshold operational in England imposes a greater downwards pressure on price and/or volumes than the one applied by ICER in the US.